HDAC inhibitor, MS-275, increases vascular permeability by suppressing Robo4 expression in endothelial cells. Issue 3 (3rd July 2021) - Kashio, Taito; Shirakura, Keisuke; Kinoshita, Mayumi; Morita, Maaya; Ishiba, Ryosuke; Muraoka, Kosuke; Kanbara, Tomoaki; Tanaka, Masato; Funatsu, Risa; Hino, Nobumasa; Koyama, Shohei; Suzuki, Ryo; et al.
ABSTRACT: Roundabout guidance receptor 4 (Robo4) is an endothelial-specific membrane protein that suppresses pathological angiogenesis and vascular hyperpermeability by stabilizing endothelial cells. Robo4 suppresses severe systemic inflammation induced by pathogens and endotoxins and inhibits tumor growth and metastasis, therefore serving as a potential therapeutic target. Although the regulation of Robo4 expression through transcription factors and epigenetic mechanisms has been studied, the role of histone deacetylases (HDACs) has not been explored. In the present study, we investigated the involvement of HDACs in the regulation of Robo4 expression. An HDAC inhibitor, MS-275, which inhibits HDAC1, HDAC2, and HDAC3, was found to suppress Robo4 expression in endothelial cells. Small interfering RNA (siRNA)-mediated knockdown of HDAC3, but not of HDAC1 and 2, also decreased its expression level. MS-275 downregulated the expression of the transcription factor complex GABP, in addition to suppressing Robo4 promoter activity. GABP expression was also downregulated by the siRNA against HDAC3. MS-275 decreased the transendothelial electrical resistance of a monolayer of mouse endothelial cells and increased the rate of leakage of Evans blue dye in the mouse lungs. In addition, MS-275 accelerated cell migration through the endothelial cell monolayer and augmented cell extravasation in the mouse lungs. Taken together, we demonstrated that MS-275 suppresses Robo4 expression by inhibiting HDAC3 in endothelial cells and enhances endothelial and vascular permeability. Thus, we demonstrated a novel mechanism regulating Robo4 expression and vascular permeability, which is anticipated to contribute to future therapies for infectious and inflammatory diseases.